(untitled) (REMUNOM, 2026)
This article aims to analyze the role of Criminal Law in the Amazonian context from the perspective of critical criminology, with an emphasis on penal selectivity and the structural inequalities that permeate the region. It is based on the understanding that the penal system does not operate in a neutral manner, but rather tends to reproduce patterns of social control directed, above all, at the most vulnerable populations. In this sense, critical criminology offers important theoretical instruments to understand how the state’s punitive power manifests in contexts marked by social inequality, institutional precariousness, and structural fragilities. The Amazon region presents social, economic, and territorial specificities that directly influence the incidence of the penal system, especially regarding peripheral and traditional populations. Based on a literature review and critical analysis, the study seeks to reflect on the mechanisms of penal selectivity and their implications within the regional context. It concludes that understanding the dynamics of the penal system in the Amazon requires a critical approach that considers the historical and structural inequalities present in the region.